\(x^5+x+1=\) help me pz

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

24 tháng 7 2021

x5  + x + 1 = x5 - x2 + x2 + x + 1 

= x2(x3 - 1) + (x2 + x + 1) 

= x2(x - 1)(x2 + x + 1) + (x2 + x + 1) 

= (x2 + x  + 1)[x2(x - 1) + 1]

= (x2 + x  + 1)(x3 - x2 + 1) 

24 tháng 7 2021

Thank you

20 tháng 11 2019

\((\frac{3x}{x+3}+\frac{2}{x-5}):\frac{1}{\left(x-5\right)\left(x+3\right)}\)

ĐK : x \(\ne-3,\) x \(\ne5\)

\(\Leftrightarrow\left[\frac{3x\left(x-5\right)}{\left(x+3\right)\left(x-5\right)}+\frac{2\left(x+3\right)}{\left(x-5\right)\left(x+3\right)}\right]:\frac{1}{\left(x+3\right)\left(x-5\right)}\)

\(\Leftrightarrow\left[\frac{3x^2-15x+2x+6}{\left(\right)\left(\right)}\right]:\frac{1}{\left(\right)\left(\right)}\)

\(\Leftrightarrow\left[\frac{3x^2-13x+6}{\left(x-5\right)\left(x+3\right)}\right].\left(x+3\right)\left(x-5\right)\)

\(\Leftrightarrow3x^2-13x+6\)

7 tháng 6 2019

\(a,\)\(x^5+x+1\)

\(=x^5-x^2+x^2+x+1\)

\(=x^2\left(x^3-1\right)+\left(x^2+x+1\right)\)

\(=x^2\left(x-1\right)\left(x^2+x+1\right)+\left(x^2+x+1\right)\)

\(=\left(x^2+x+1\right)\left(x^3-x^2+1\right)\)

7 tháng 6 2019

\(b,\)\(x^5+x^4+1\)

\(=x^5+x^4+x^3-x^3+1\)

\(=x^3\left(x^2+x+1\right)-\left(x-1\right)\left(x^2+x+1\right)\)

\(=\left(x^2+x+1\right)\left(x^3-x+1\right)\)

9 tháng 7 2019

undefined

9 tháng 7 2019

undefined

21 tháng 7 2016

a)\(\frac{2x-5}{x+5}\)=3 ĐKXĐ: x khác -5

=> 2x-5=3(x+5)

<=>2x-5=3x+15

<=>-x=20

<=>x =-20

 

21 tháng 7 2016

b)\(\frac{x2-6}{x}\)=x+\(\frac{3}{2}\)ĐKXĐ\(x\ne0\)

=>2(x2-6)=2x2+3x

<=>2x2-12=2x2+3x

<=>-3x=12

<=>x=-4

15 tháng 9 2017

a, \(=x^5+x^4+x^3-x^4-x^3-x^2+x^2+x+1\)

      \(=x^3\left(x^2+x+1\right)-x^2\left(x^2+x+1\right)+\left(x^2+x+1\right)\)

       \(=\left(x^2+x+1\right)\left(x^3-x^2+1\right)\)

NV
15 tháng 3 2019

ĐKXĐ: \(x>0\)

\(S=\left(\frac{1}{\sqrt{x}}+\frac{\sqrt{x}}{\sqrt{x}+1}\right)\div\left(\frac{\sqrt{x}}{x+\sqrt{x}}\right)=\left(\frac{1}{\sqrt{x}}+\frac{\sqrt{x}}{\sqrt{x}+1}\right)\left(\frac{\sqrt{x}\left(\sqrt{x}+1\right)}{\sqrt{x}}\right)\)

\(=\left(\frac{1}{\sqrt{x}}+\frac{\sqrt{x}}{\sqrt{x}+1}\right)\left(\sqrt{x}+1\right)=\frac{\sqrt{x}+1}{\sqrt{x}}+\sqrt{x}=\frac{x+\sqrt{x}+1}{\sqrt{x}}\)